Why Oil Wil Cost $5 per Barrel in 2010 - Grosse, Robert; Yares, Yuan (Tufts Archival Research Center, 2005)
Volume 25, Issue 1. Winter Grosse and Yafies argue that improved technologies will decrease the cost of oil extraction, thus increasing supply, while the development of alternate energy sources will reduce the demand for oil. The interaction of these two forces will lead to a much lower oil price in the near future.